Climatology of the CO Vertical Distribution on Mars Based on ACS TGO Measurements. Issue 9 (25th September 2022) - Fedorova, Anna; Trokhimovskiy, Alexander; Lefèvre, Franck; Olsen, Kevin S.; Korablev, Oleg; Montmessin, Franck; Ignatiev, Nikolay; Lomakin, Alexander; Forget, Francois; Belyaev, Denis; Alday, Juan; Luginin, Mikhail; et al.
Abstract: Carbon monoxide is a non‐condensable gas in the Martian atmosphere produced by the photolysis of CO2 . Its abundance responds to the condensation and sublimation of CO2 from the polar caps, resulting in seasonal variations of the CO mixing ratio. ACS onboard the ExoMars Trace Gas Orbiter have measured CO in infrared bands by solar occultation. Here we provide the first long‐term monitoring of the CO vertical distribution at the altitude range from 0 to 80 km for 1.5 Martian years from Ls = 163° of MY34 to the end of MY35. We obtained a mean CO mixing ratio of ∼960 ppmv at latitudes from 45°S to 45°N and altitudes below 40 km, mostly consistent with previous observations. We found a strong enrichment of CO near the surface at Ls = 100–200° in high southern latitudes with a layer of 3, 000–4, 000 ppmv, corresponding to local depletion of CO2 . At equinoxes we found an increase of the CO mixing ratio above 50 km to 3, 000–4, 000 ppmv at high latitudes of both hemispheres explained by the downwelling flux of the Hadley circulation on Mars, which drags the CO enriched air. General circulation models tend to overestimate the intensity of this process, bringing too much CO. The observed minimum of CO in the high and mid‐latitudes southern summer atmosphere amounts to 700–750 ppmv, agreeing with nadir measurements. During the global dust storm of MY34, when the H2 O abundance peaks, we see less CO than during the calm MY35, suggesting an impact of HOx chemistry on the CO abundance. Plain Language Summary: Carbon monoxide (CO) is a product of the photodissociation of the main component of the Martian atmosphere, CO2 (96%). During the polar night on Mars, the temperature drops so low that ∼30% of the global atmospheric carbon dioxide freezes out, condensed into snowflakes. They settle to the ground to form a seasonal polar cap, which sublimates in spring. Unlike CO2, CO is not a condensable species, so its relative abundance increases when CO2 and the atmospheric pressure drops, forming a prominent seasonal cycle. This behavior of CO was well documented by spacecraft measurements of column abundances, while its vertical distribution remained poorly known until recently. Still, it helps to separate the impacts of atmospheric dynamics and chemistry, addressing the problem of the Martian atmosphere's stability. We present the first climatology of the CO vertical distribution lasting more than one Martian year based on solar occultations by the ExoMars Trace Gas Orbiter. We report a previously unobserved CO layer near the surface in high southern latitudes in late winter and spring and document the difference between two Martian years caused by the global dust storm. These observations give new challenges to General Circulation Models for understanding the modern atmosphere of Mars. Key Points: The first climatology of CO vertical profiles is collected for the period Ls = 163° of Martian Year 34 to the end of Martian Year 35 The mean CO volume mixing ratio is ∼960 ppmv at 0–35 km and 45°S–45°N Strong enrichment of CO, >3, 000 ppmv, is detected at 10–20 km at Ls = 100–200 in high southern latitudes and above 50 km at equinoxes near Poles